An Application of Keystone Perforator Island Flap for Closure of Lumbosacral Myelomeningocele Defects. Issue 3 (September 2016) - Park, Hye-Sung; Morrison, Edwin; Lo, Cheng; Leong, James
Abstract : Abstract: Myelomeningocele, also known as spina bifida, is the commonest form of neural tube defect in which both meninges and spinal cord herniate through a large vertebral defect. It may be located at any spinal level; however; lumbosacral involvement is most common. After birth, the closure of spinal lesion is preferably undertaken in the first 48 hours to minimize the risk of injury and central nervous system infection. Relatively small skin defects overlying the dural repair may be directly closed. However, larger defects require reconstructive closure. Numerous methods of reconstruction have been described, such as split skin graft, local flaps or lumbosacral fasciocutaneous flaps, muscle flaps using latissimus dorsi, gluteal or paraspinous muscles, and perforator flaps namely superior gluteal artery perforators, and dorsal intercostal artery perforator flaps. At Monash Health, Victoria, we have used the keystone perforator island flaps to reconstruct lumbosacral myelomeningocele defects on 5 newborns between January 2008 and January 2014. This article evaluates the short-term and long-term outcomes of these patients who were followed up for 10 to 66 months.